Sucroquímica: síntese e potencialidades de aplicações de alguns derivados químicos de sacarose - Boscolo, Maurício [UNESP] (Sociedade Brasileira de Química, 2003)
The interest on the use of sucrose as raw material increased in the last years. In this work, the synthesis and applications of sucrose derivatives as esters, ethers, and other products are discussed in a concise manner aiming to presenting the sucrochemistry as a promising field in organic chemistry from a rather accessible, low-priced, ecological, and renewable source.
Sucrochemistry: synthesis and potentialities for applications of some sucrose chemical derivates
Keywords: Sucrose; Sucrochemistry; Sugarcane